Endosomal phosphatidylserine is critical for the YAP signalling pathway in proliferating cells - Tatsuyuki Matsudaira (Nature Portfolio, 2017)
Yes-associated protein (YAP) is a growth-promoting transcription co-activator that regulates the malignancy of various cancers, however its regulation is not fully understood. Here the authors show that phosphatdylserine at recycling endosomes regulates YAP signalling pathway.